2006
DOI: 10.1099/mic.0.29195-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-enabled analysis of the utilization of taurine as sole source of carbon or of nitrogen by Rhodobacter sphaeroides 2.4.1

Abstract: In the present study, R. sphaeroides 2.4.1 was found to grow exponentially with taurine as the sole source of carbon and energy for growth. When taurine was the sole source of nitrogen in succinate-salts medium, the taurine was rapidly degraded, and most of the organic nitrogen was excreted as the ammonium ion, which was then utilized for growth. Most of the enzymes involved in dissimilation, taurine dehydrogenase (TDH), sulfoacetaldehyde acetyltransferase (Xsc) and phosphate acetyltransferase (Pta), were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Taurine dehydrogenase (TauXY) activity could be measured in cell extracts of taurine-grown cells only (Table 2). This corresponded to the inducibility of this enzyme noted elsewhere (Brüggemann et al, 2004;Denger et al, 2006b). Sulfoacetaldehyde acetyltransferase (Xsc) was active in extracts from all sulfonate-grown cells, and absent in extracts from acetate-grown cells (Table 2).…”
Section: Methodsmentioning
confidence: 97%
“…Taurine dehydrogenase (TauXY) activity could be measured in cell extracts of taurine-grown cells only (Table 2). This corresponded to the inducibility of this enzyme noted elsewhere (Brüggemann et al, 2004;Denger et al, 2006b). Sulfoacetaldehyde acetyltransferase (Xsc) was active in extracts from all sulfonate-grown cells, and absent in extracts from acetate-grown cells (Table 2).…”
Section: Methodsmentioning
confidence: 97%
“…Taurocholate was found to be a source of taurine for Bilophila wadsworthia RZATAU (Schumacher et al 1996;Laue et al 1997), but neither taurocholate nor cholate was determined, and Communicated by Walter Reinecke. the pathway of taurine degradation in B. wadsworthia is still incompletely understood. However, an understanding of taurine degradation in other organisms has proceeded further (Cook andDenger 2002, 2006;Denger et al 2006;Gorzynska et al 2006;Cook et al 2007): relevant pathway variants have been found in Delftia acidovorans SPH-1 and in C. testosteroni KF-1 (see below). An understanding of cholate degradation is also being developed (Philipp et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The regulator, TauR has been associated with (1) taurine degradative genes since their discovery (e.g., Ruff et al 2003;Brüggemann et al 2004;Denger et al 2006;Gorzynska et al 2006;Baldock et al 2007), with (2) assimilation of taurine nitrogen in R. palustris CGA009 (Denger et al 2004b) (where the same genes [RPB_1035-RPB_1039] are found in R. palustris strains HaA2 and TIE-1), and with (3) assimilation of taurine sulfur, where direct evidence of the function of TauR as a regulatory protein is available (Wiethaus et al 2008). We detected two tauR-like genes (MED92_03198 (tauR2) and MED92_13211 (tauR1)) in the genome of N. caesariensis MED92, and we provisionally annotated the eight open reading frames (ORFs) in the flanking regions ( Fig.…”
Section: Resultsmentioning
confidence: 99%